Linear association of compound dietary antioxidant index with hyperlipidemia: a cross-sectional study - Zhou, Haoran; Li, Tianshu; Li, Jie; Zheng, Dongdong; Yang, Jie; Zhuang, Xin (Frontiers in Nutrition, 2024)
There is growing evidence that antioxidant-rich diets may prevent hyperlipidemia.However, the relationship between the Composite Dietary Antioxidant Index (CDAI) and hyperlipidemia is unclear. CDAI is a composite score reflecting the antioxidant content of an individual's diet, and this study aimed to investigate the relationship between CDAI and hyperlipidemia.The study used the 2003-2018 National Health and Nutrition Examination Survey (NHANES) database for cross-sectional analyses and included 27,626 participants aged 20 years and older.The CDAI,which includes vitamins A,C, and E, zinc, selenium, and carotenoids, was calculated based on dietary intake reported in a 24-hour recall interview. Hyperlipidaemia was defined by the National Cholesterol Education Program (NCEP). Covariates included age, sex, race, education, marriage, household poverty-to-income ratio (PIR), glomerular filtration rate (eGFR), body mass index(BMI),energy,carbohydrates, total fat, cholesterol, smoking, alcohol consumption, hypertension, diabetes mellitus, coronary heart disease, and lipid-lowering medications.The association between CDAI and hyperlipidemia was explored through multiple logistic regression analyses and smoothed curve fitting. We also performed subgroup analyses and interaction tests to verify the relationship's stability.After adjusting for potential confounders, CDAI was negatively associated with the risk of developing hyperlipidemia (OR 0.98, 95% CI 0.96-0.99,p<0.01). The results of weighted regression models stratified by quartiles of CDAI (-8.664 ≤ Q1 ≤ -2.209,-2.209 < Q2 ≤ -0.002, -0.002 < Q3 ≤ 2.774,2.774 < Q4 ≤ 124.284), fully adjusted for confounding variables, indicated that compared with the bottom quartile (Q1) of the CDAI, Q2, Q3 and Q4 of participants had a lower advantage ratio (Q2: OR 0.91,95% CI 0.78-1.06,p<0.21; Q3: OR 0.85, 95% CI 0.73-1.00,p<0.05; and Q4: OR 0.77, 95% CI 0.64-0.94,p<0.01), which was confirmed by a test for trend (p < 0.05). Smoothed curve fit analysis showed linearity (p for non-linear = 0.0912). In summary, there is a linear negative relationship between CDAI and the risk of developing hyperlipidemia. Subgroup analyses by age, sex, ethnicity, education level, marriage, tobacco status, alcoholic drinking, body mass index(BMI), hypertension, and diabetes did not indicate strong interactions.In this large cross-sectional study, there was a linear negative association between CDAI and hyperlipidemia among US adults.Therefore increase antioxidant rich foods in your life as a prevention of hyperlipidaemia.